1987
DOI: 10.1300/j082v13n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sexual Orientation by Heterosexuals and Homosexuals

Abstract: The purpose of this study was to determine if sexual orientation can be correctly identified under controlled conditions. A series of 24 brief videotaped interviews with homosexual and heterosexual men and women were presented to a sample of 143 subject raters divided into four sexual preference and gender groups. None of the groups were able to exceed levels of correct detection. Approximately 20% of the total subject pool did exceed chance levels. There were significantly more women than men in this sub-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 0 publications
1
33
2
Order By: Relevance
“…In contrast to some other studies (Ambady et al, 1999;Berger et al, 1987;Sylva et al, 2007), homosexual raters were not generally more accurate. As we noted, however, the accuracy advantage of homosexual raters found in those studies was modest and somewhat inconsistent.…”
Section: Measurecontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast to some other studies (Ambady et al, 1999;Berger et al, 1987;Sylva et al, 2007), homosexual raters were not generally more accurate. As we noted, however, the accuracy advantage of homosexual raters found in those studies was modest and somewhat inconsistent.…”
Section: Measurecontrasting
confidence: 87%
“…Some studies of thin slices of behavior have included relevant data for evaluating this belief. One study found that homosexual people were better than heterosexuals at accurately judging sexual orientation from brief videotaped interviews (Berger, Hank, Rauzi, & Simkins, 1987;results reported in Ambady et al, 1999). Ambady et al (1999) found inconsistent results across two studies regarding the relative accuracy of heterosexual and homosexual raters; in general, results did not reveal that either was superior.…”
Section: Individual Differences In Rating Accuracymentioning
confidence: 96%
“…Biased social categorization is likely when there are no salient categorical features defining a person's group membership. For example, the categorization of a person as 'Jewish' or 'gay' is less reliable than the categorization of a person as black or white, male or female (Berger, Hank, Rauzi & Simkins, 1987;Elliott & Wittenberg, 1955). Suppose an observer uses attributes of uncertain cue validity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identifying someone who is gay holds numerous social implications, such as rejection, discrimination, and prejudice (Herek, 2004), with a high potential impact for the target's safety and well-being (e.g., Herek, Cogan, & Gillis, 2002). Berger, Hank, Rauzi, and Simkins (1987) set out to investigate if sexual orientation could be identified at better than chance levels. Video stimuli were created from brief interviews with 24 gay and straight men and women (i.e., 6 targets in each gender × sexual preference combination) presented to 143 judges.…”
Section: "Gaydar"mentioning
confidence: 99%